Assesment of Markers of Endothelial Dysfunction and Myocardial Stress in Patients with Hypertrophic Cardyomyopathy - F. M. Bogatyreva; V. Yu. Kaplunova; M. V. Kozhevnikova; G. A. Shakaryants; D. A. Yatsenko; А. V. Emelianov; A. S. Lishuta; N. V. Khabarova; E. V. Privalova; Yu. N. Belenkov (Рациональная фармакотерапия в кардиологии)
Aim. To study the level of serum biomarkers of endothelial dysfunction and myocardial stress in patients with various types of hypertrophic cardiomyopathy (HCM).Material and Methods. 48 patients with hypertrophic cardiomyopathy (27 men and 21 women) were examined, the mean age was 54±13 years. The patients were divided into two groups according to the course options: group 1 - symptomatic stable course (n=14); group 2 - progressive course of symptomatic HCM (n=34). In accordance with the assigned tasks, all patients underwent determination of biological markers of neurohumoral systems in blood serum using immunofluorescence assay analysis: N-terminal fragment of brain natriuretic peptide (NT-proBNP), von Willebrand factor (vWF), endothelin-1, E-selectin with subsequent evaluation and correlation of results with clinical and instrumental characteristics of patients. When performing echocardiography following parameters were assessed: dimensions of the heart chambers, the thickness of the interventricular septum, the thickness of the posterior wall of the left ventricle (LV), LV mass, LV mass index, the ratio between LV filling in diastole (peak E) and atrial systole (peak A)-(E/A), relative myocardial thickness index, left atrial volume index.Results. Both groups showed increased levels of NT-proBNP and endothelin-1. E-selectin and vonWillebrand factor remained within the normal range. There was no statistically significant intergroup difference. There was a correlation between the level of the index of the relative myocardial thickness and the level of NT-proBNP (r=0.30; p=0.04). A correlation was found between the level of the vWF marker and the left atrial volume index (r=0.32; p=0.04). When assessing the association of indicators of intracardiac hemodynamics with other markers (E-selectin and endothelin-1, no statistically significant relationships were found.Conclusion. In the course of the research, it was found that the high activity of endothelin-1 and NT-proBNP reflects endothelial dysfunction and myocardial stress in patients with HCM, especially in patients with a progressive variant of HCM. However, we did not find any changes in the levels of E-selectin and von Willebrand factor, as well as their intergroup differences. These results require additional studies to assess endothelial dysfunction in patients with HCM.